Regulatory rewiring of Dand5 drove left–right organizer heterotopy and organ asymmetry evolution in chordates - Rongrong Pan; Jiaqi Zou; Yanhong Chen; Qiuning Yan; Yanhong Zhong; Qingming Qu; Guang Li (Proceedings of the National Academy of Sciences, 2026)
Heterotopy—the spatial relocation of developmental processes—is a key mechanism driving morphological innovation, yet its underlying regulatory basis remains poorly understood. In chordates, the left–right (L–R) organizer shifted from the anterior domain as represented by amphioxus to the posterior end in vertebrates, accompanied by a coordinated relocation of the entire L–R gene regulatory network (GRN), including Dand5 and its downstream genes Nodal , Lefty, and Pitx . Here, we dissect the regulation of Dand5 in amphioxus and compare it with vertebrates. We show that L–R asymmetry of amphioxus Dand5 is established transcriptionally and not posttranscriptionally as in vertebrates. Its transcription is directly activated by Hedgehog signaling and repressed by Wnt signaling, independent of vertebrate-specific inputs from Brachyury, and Notch and Wnt signaling. However, key elements required for postregulation of vertebrate Dand5 asymmetry, including the responsiveness of its 3’-untranslated region (UTR) to Bicc1-mediated RNA repression and Bicc1 expression in embryonic posterior end, seem already present in amphioxus. Our study therefore provides empirical evidence that repurposed regulatory sequences can drive heterotopy of developmental GRNs, offering a mechanistic explanation for the evolutionary shift of the LR signaling center and a foundation for exploring the diversification of LR organs across chordates.